COVID-19 Pandemic: Trends, Interventions and Outcomes experienced at Allied Hospitals of Rawalpindi Medical University Pakistan - Umar, Muhammad; Shahid, Rizwana; Zafar, Raja Bilal; Zeb, Shazia; Aziz, Qaiser; Akram, Muhammad Omar; Mustafa, Sara; Khan, Muhammad Mujeeb; Khurram, Muhammad; Fazal-ur-Rahman; Khalid, Muhammad Ali; Ambreen, Saima; et al. (Infectious Diseases Journal of Pakistan, 2022)
Objectives: To determine the trend of COVID-19 cases, the effects of the interventions done to limit the spread of coronavirus and outcomes achieved during COVID-19 pandemic at Rawalpindi city. Subjects & Methods: A cross-sectional study was conducted at four tertiary care hospitals (Holy Family Hospital, Benazir Bhutto Hospital, District Head Quarters Hospital & Rawalpindi Institute of Urology & Transplantation) and two field hospital established on emergency basis through consecutive sampling. The data was gathered from mid-March till first week of July 2020 regarding their management (oxygen supply or placement on ventilators) and mortality. The data was analyzed by SPSS version 25.0. Results: 28,208 study subjects presented with coronavirus associated symptoms and screened at filter clinics established in tertiary care and field hospitals affiliated and managed by Rawalpindi Medical University. Out of 4,106 suspected cases, 2119 were found to have confirmed COVID-19. Adequate number of beds and equipment including ventilators and oxygen cylinders were arranged in phases to tackle with patient burden as medical interventions. Lock down imposition constituted nonpharmacological intervention. Total 357 deaths were reported with highest frequency (65.3%) of males. Initially people were asymptomatic and stable but later were reported with severe symptoms of COVID-19. Peak of cases were detected about 10-14 days after lockdown lifting and Eid Festival. Conclusion: Medical as well as non-medical interventions seemed to be quite effective in limiting the spread of COVID-19. Keywords: COVID-19, Trends, Interventions, Outcomes, Ventilators, Lockdown, Social distancing, Hand sanitization.